2020
DOI: 10.1016/j.jallcom.2020.154509
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, electronic, bonding, and optical properties of topological CaSn3 semimetal

Abstract: In recent days, topological semimetals have become an active branch of materials research. The topological Weyl semimetal CaSn 3 , belonging to the AuCu 3 type cubic structure, is an important electronic system to investigate both from the point of view of fundamental physics and prospective applications. In this work, we have studied the structural, elastic, mechanical, electronic, bonding, Fermi surface and optical properties of CaSn 3 in detail via first-principles method using the density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 87 publications
2
40
0
Order By: Relevance
“…The calculated values of hardness of TaP and TaAs are 18.07GPa and 14.07 GPa, respectively. It is seen from Table 3 that compared to other well-known WSMs [5][6][7] , the elastic moduli of TaX are significantly larger.…”
Section: Results and Analysismentioning
confidence: 90%
See 4 more Smart Citations
“…The calculated values of hardness of TaP and TaAs are 18.07GPa and 14.07 GPa, respectively. It is seen from Table 3 that compared to other well-known WSMs [5][6][7] , the elastic moduli of TaX are significantly larger.…”
Section: Results and Analysismentioning
confidence: 90%
“…It is important to note that we have not included SOC in our electronic band structure calculations. A number of previous studies on variety of topological WSMs and topological insulators [5][6][7]135 belonging to different crystal classes have demonstrated that, as far as the bulk physical properties described in this work are concerned, inclusion of SOC has only a minimal effect. None of the conclusions drawn from our investigation is affected significantly by the SOC.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations